Treatment Dilemmas for Vulnerable Patients in Oral Health Clinical and Ethical Issues - Mersel, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book equips the reader with a sound understanding of the treatment of neglected and vulnerable patients in the dental office. It offers a comprehensive multidisciplinary approach to atraumatic carious treatment, minimal intervention dentistry, TMJ affections and nutritional consequences. Maintaining proper oral health includes managing of oral hygiene, healthy diet and seeking for a treatment when needed. Untreated dental disease can have a significant adverse impact on the health, wellbeing and quality of life. This book helps practitioners to understand and address the needs of dental neglected adults and children, and guide them through prevention procedures, diagnostics and treatment planning. Important techniques like physiologic impression for removable denture, single crown impression, digital planning and prosthodontic bridges are explained, and socio-demographic and economic changes in Oral Health are discussed. The comprehensive coverage of the topic and the evidence based references make this book a must have for dental practitioners.
Chapter 1: Oral Health: Ethical and Clinical Concerns -- Chapter 2: Prevention for Vulnerable Patients: Atraumatic Carious Treatment and Mild-To-Moderate Periodontal Therapy -- Chapter 3: Dental Neglect -- Chapter 4: The Vulnerable Patients Group: The Global Oral Health Concept -- Chapter 5: The TMJ Troubles and Their Nutritional Consequences -- Chapter 6: Prevention Strategy - A Practical Protocol for Elderly Patients.
Keywords: Dentistry; Medical Ethics; Dentistry; Medical Ethics; Mouth Diseases -- therapy; Dental Health Services -- organization & administration; Health Services Accessibility; Medically Underserved Area; Vulnerable Populations; Poverty Areas; Oral Health